Zero Waste in apparel industry: limitations and alternatives - Italiano, Isabel Cristina; Kauvauti, Lílian Sayuri; Marcicano, João Paulo Pereira (Sustainability in Debate, 2022)
Zero Waste approach applied to garment manufacturing promises the elimination of textile waste in the production process, with actions towards sustainability. In this perspective, this article identifies critical aspects and limitations of the design and the pattern making process using Zero Waste approach, aiming its application in the garment industry, with large-scale production. The study initiates with zero waste bibliography research and theoretical and experimental analysis of the proposals of the fashion designers who use Zero Waste approach to garment design and pattern making. As results, the article presents critical aspects and limitations of the approach, and discuss viable alternatives for its implementation in the large-scale garment manufacturing process.